Pengaruh Promosi, Harga, dan Kualitas Produk terhadap Kepuasan Konsumen : Studi Kasus pada Usaha Bananamoo Kediri (International Forum of Researchers and Lecturers, 2025)
Customer satisfaction is a crucial factor in determining the success and sustainability of a business. Satisfaction can be enhanced through various strategic approaches, such as effective promotional activities, competitive pricing, and consistent product quality to meet or even exceed consumer expectations. This study aimed to determine the effect of promotion, price, and product quality on customer satisfaction at Bananamoo Kediri. This study employed a quantitative method, collecting data through distributing questionnaires to 25 respondents selected using accidental sampling, namely consumers who happened to come and were willing to be sampled. The collected data were then analyzed using multiple linear regression to test partial and simultaneous relationships between variables. The results showed that promotion significantly influenced customer satisfaction, indicating that the better the promotional strategy implemented, the higher the level of consumer satisfaction. Similarly, price had a partially significant effect, indicating that consumers tend to be satisfied if the price offered is commensurate with the quality and benefits of the product. Product quality was also shown to have a partially significant effect on customer satisfaction, underscoring the importance of consistent quality in maintaining consumer trust. Simultaneously, the three independent variables—promotion, price, and product quality—had a positive effect on customer satisfaction. This finding is supported by the coefficient of determination (R²) of 80.3%, indicating that variations in customer satisfaction (Y) can be explained by the three variables (X) together, while the remainder is influenced by other factors outside this study. Thus, this study emphasizes the importance of managing a balanced marketing strategy to increase customer satisfaction and loyalty.